INTERNATIONAL MECHANISMS FOR THE ENFORCEMENT OF JUDGEMENTS OF THE INTERNATIONAL COURT OF JUSTICE - Arakelyan, Roza (State and Law, 2025)
The authority and competence of the International Court of Justice has been the subject of considerable debate in recent years, in particular on the effectiveness of the Court in enforcing its judgements. The lack of clear mechanisms for enforcing the judgements of the International Court of Justice has led to a crisis in their enforcement. Taking into account the above, the aim of this article is to investigate the international enforcement mechanisms of the International Court of Justice, through which comprehencively have been analysed Article 94 of the United Nations Charter, as well as the competence of the General Assembly and the Secretary-General with regard to enforcement as alternative international mechanisms. Perhaps an international mechanism for the enforcement of ICJ judgements is provided for in Article 94 of the UN Charter, but based on the wording of the said Article, it cannot be argued that only the UN Security Council has the exclusive power to enforce an ICJ judgement. According to the UN Charter, in order to enforce the judgement of the International Court of Justice, the General Assembly may establish a subsidiary body, as well as adopt resolutions aimed at implementing the judgements of the International Court of Justice. In addition, the UN Secretary General is also obliged to enforce the judgement under Articles 98 and 99 of the UN Charter. The latter is authorised to bring to the attention of the Security Council any matter which, in his opinion, may threaten international peace and security. The role of the secretary-general should not be overlooked when it comes to the enforcement of judgements of the International Court of Justice.